MENGGALI POTENSI DIGITAL UNTUK MENINGKATKAN POPULARITAS WISATA ALAM BISEANG LABBORO - Damianus, Erick; Saeni, Asrini A. (Politeknik STIA LAN Makassar, 2024)
This objective of the study was to evaluate the digital promotion strategy of Biseang Labboro Nature Tourism in Maros Regency, managed by the Bantimurung Bulusaraung National Park. A descriptive qualitative method was used to collect data through field observations, interviews with management staff, ecotourism operators, and tourists, as well as document analysis. The results of the study indicated that promotion through social media, such as Instagram, has not been fully optimized. The main obstacles are limited resources and a lack of coordination among relevant parties. This study adopts the AISAS model (Attention, Interest, Search, Action, Share) to analyze the effectiveness of promotions and audience interaction with tourism information. The model offers a systematic approach to attract attention, build interest, encourage information search, motivate visit actions, and promote the sharing of positive experiences. Findings show that attractive promotional videos with strong visual elements and narratives significantly increased viewer engagement. The study recommends improving the quality of digital content to expand promotion reach and attract more tourists, so that this unique nature tourism potential can be more widely recognized. The findings are expected to serve as a reference for marketing strategies of other tourist destinations in Indonesia.